Inhibiting phosphoglycerate dehydrogenase counteracts chemotherapeutic efficacy against MYCN‐amplified neuroblastoma. Issue 5 (17th December 2020) - Arlt, Birte; Zasada, Christin; Baum, Katharina; Wuenschel, Jasmin; Mastrobuoni, Guido; Lodrini, Marco; Astrahantseff, Kathy; Winkler, Annika; Schulte, Johannes H.; Finkler, Sabine; Forbes, Martin; Hundsdoerfer, Patrick; et al.
Abstract: Here we sought metabolic alterations specifically associated with MYCN amplification as nodes to indirectly target the MYCN oncogene. Liquid chromatography‐mass spectrometry‐based proteomics identified seven proteins consistently correlated with MYCN in proteomes from 49 neuroblastoma biopsies and 13 cell lines. Among these was phosphoglycerate dehydrogenase (PHGDH), the rate‐limiting enzyme in de novo serine synthesis. MYCN associated with two regions in the PHGDH promoter, supporting transcriptional PHGDH regulation by MYCN. Pulsed stable isotope‐resolved metabolomics utilizing 13 C‐glucose labeling demonstrated higher de novo serine synthesis in MYCN ‐amplified cells compared to cells with diploid MYCN . An independence of MYCN ‐amplified cells from exogenous serine and glycine was demonstrated by serine and glycine starvation, which attenuated nucleotide pools and proliferation only in cells with diploid MYCN but did not diminish these endpoints in MYCN ‐amplified cells. Proliferation was attenuated in MYCN ‐amplified cells by CRISPR/Cas9‐mediated PHGDH knockout or treatment with PHGDH small molecule inhibitors without affecting cell viability. PHGDH inhibitors administered as single‐agent therapy to NOG mice harboring patient‐derived MYCN ‐amplified neuroblastoma xenografts slowed tumor growth. However, combining a PHGDH inhibitor with the standard‐of‐care chemotherapy drug, cisplatin, revealed antagonism of chemotherapy efficacy in vivo. Emergence of chemotherapy resistance was confirmed in the genetic PHGDH knockout model in vitro. Altogether, PHGDH knockout or inhibition by small molecules consistently slows proliferation, but stops short of killing the cells, which then establish resistance to classical chemotherapy. Although PHGDH inhibition with small molecules has produced encouraging results in other preclinical cancer models, this approach has limited attractiveness for patients with neuroblastoma. Abstract : Whats's new? Molecular alterations in neuroblastoma influence disease aggressiveness and relapse risk. In particular, molecular amplification of the oncogene MYCN is a major determinant of patient outcome. Here, shotgun proteomics was combined with metabolomics to investigate alterations in MYCN as potential therapeutic targets in neuroblastoma. A strong correlation was detected between MYCN amplification and proteins involved in serine synthesis, including the rate‐limiting enzyme PHGDH, and one‐carbon metabolism. Targeting PHGDH by genetic knockout and small molecule inhibitors stalled proliferation but did not kill neuroblastoma cells. Chemotherapeutic resistance was evident in mice with patient‐derived neuroblastoma xenografts following treatment with PHGDH inhibitors and cisplatin.